Improvement of wheat abiotic stress resistance via genetic transformation - Pauk, János (Acta Biologica Szegediensis, 2002)
Aldose reductase gene (ALR) isolated from alfalfa (MsALR), was constructed into a plant expression vector (pAHC), and then named as pAHALR. Wheat suspension culture was bombarded with this plasmid and the transformed calli were cultured and selected on medium containing 10mg/L Bialaphos (15% glufozinate-ammonium) as a selective agent. For the molecular analysis of putative transgenic samples, PCR, Southern and Western blots were carried out. Also aldose reductase enzyme activity was detected by HPLC only in the transgenic callus samples by the accumulation of sorbitol, which is the end product of aldose reductase catalyzed glucose reduction reaction. Protective function of ALR was verified by malondialdehyde analysis under stress condition. The activity of the ALR gene will also be investigated on the transgeneic plants by biochemical and physiological analysis.